VD_FINDINFO Jug / 2012 / 105 vom 18. Oktober 2011 - VD Tribunal cantonal (2011)
DÉPENS, FIXATION DE LA PEINE, PRÉSOMPTION D'INNOCENCE, ABUS DE CONFIANCE | 138 CP, 47 CP, 10 CPP (CH), 433 al. 1 CPP(CH), 433 al. 2 CPP (CH)